Copart's and IAAI's - Adel, Mohamed (Faculty of Information Technology, 2019)
it's a program which is made for calculating the Copart's and IAAI's final prices after the bidding like the Taxs and Local shipping from the auction yard to the international port.
it's a program which is made for calculating the Copart's and IAAI's final prices after the bidding like the Taxs and Local shipping from the auction yard to the international port.
Keywords: Programming II; OOP; VB.NET